The Misérègne slag deposit (Valle d'Aosta, Western Alps, Italy): Insights into (pre-)Roman copper metallurgy. (June 2018) - Toffolo, Luca; Addis, Anna; Martin, Silvana; Nimis, Paolo; Rottoli, Mauro; Godard, Gaston
Abstract: The Misérègne hamlet (Fénis village, Valle d'Aosta region, Italy) rises on a huge metallurgical slag deposit, whose origin has so far been unknown. Here we provide the first detailed textural, mineralogical and chemical characterization of the slags and the results of radiocarbon dating of charcoal fragments contained therein. Three types of slags are found, i.e., coarse, massive and flat, which are composed of olivine, spinel and pyroxene crystals in a glassy matrix rich in anorthite ± magnetite/ulvöspinel crystallites. All the slags contain matte droplets, which show a Cu-enrichment from the coarse and the massive slags (intermediate solid solution, ~CuFeS2, or bornite solid solution, ~Cu5 FeS4  + abundant pyrrhotite solid solution, ~Fe1−x S) to the flat slags (bornite only). Olivine morphology indicates slow cooling for the massive slags (mostly euhedral crystals), rapid cooling for the coarse slags (dendritic crystals) and slow cooling followed by quenching, consistent with tapping, for the flat slags (euhedral-dendritic transitional crystals). Bulk slag compositions and olivine-spinel geothermometry suggest that the coarse and massive slags are genetically related (T = 880–1090 °C and T = 860–1140 °C for coarse and massive slags, respectively), while the flat slags are distinct higher-temperature melts (T = 1020–1415 °C). The data suggest a multiple-step smelting process, by which an impure chalcopyrite ore, was first smelted to produce relatively Cu-poor matte and coarse and massive slags; the matte was then reprocessed at higher temperature to produce more copper metal and flat slags. Based on radiocarbon dating, the Misérègne slags date back to the II-I century BCE and thus constitute the earliest known record of metallurgical activity in the north-western Italian Alps. Highlights: We studied metallurgical slags from Misérègne (Fénis, Valle d'Aosta region, Italy). Slag compositions and geothermometry suggest a multiple-step copper smelting process. Radiocarbon dating constrains the metallurgical activity to the II-I century BCE. This is the earliest known record of copper metallurgy in the NW Italian Alps.